Personality Competence Of Islamic Religious Education (PAI) Teachers In Shaping The Character Of Students - Marita Lailia Rahman; Ali Mufron; Yeni Yeni (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
A qualified teacher must meet several competency requirements. The competencies are included pedagogic competence, personality competence, social competence, and professional competence. In this paper, the author is interested in using personality competencies among the four competencies. The purpose of this study was to find out whether there was an influence of PAI teachers' personality competence on the character of students. The research method used in this study is qualitative. The study's results above show that the personality competence of PAI teachers in building students' character has a positive and significant effect on student character formation. The basic competencies possessed by a teacher must be able to shape the character of a learner, just as a teacher must have values of discipline, responsibility, and religion. A teacher must be able to set an example to be able to achieve certain goals and be able to shape the character of a learner. Keywords: Personality Competence, PAI Teacher, Learner Character